Economic Dynamics of Mid-hilly Region of Nepal: A Systematic Review of Development Trends and Challenges - Panta, Chhatra Mani (BARUN Journal, 2026)
The mid-hilly region of Nepal, with its diverse geography and socio-economic structure, plays a pivotal role in the country’s overall economic landscape. However, this region faces several unique challenges that hinder its sustainable development. This systematic review seeks to consolidate existing literature on the economic dynamics of the mid-hilly region, focusing on key sectors such as agriculture, tourism, remittances, and infrastructure. The study critically examines the development trends, identifies the drivers of growth, and highlights the challenges impeding economic advancement. Despite its vast potential, the region remains underdeveloped due to limited access to markets, inadequate infrastructure, climate change, and a heavy reliance on remittances. The review further explores the role of agriculture in sustaining livelihoods, the growing importance of tourism, and the implications of remittance dependency on local economies. Additionally, the study assesses infrastructure gaps, especially in connectivity and energy, and their impact on regional economic activities. The findings suggest that while there are opportunities for sustainable development through integrated approaches such as eco-tourism, climate smart agriculture, and infrastructure investment, targeted interventions are required to address regional disparities. The results provide essential insights for policymakers, researchers, and development practitioners aiming to formulate strategies that foster inclusive and sustainable development in Nepal’s mid-hilly region.